Crossed McMurry Coupling Reactions for Porphycenic Macrocycles: Non‐Statistical Selectivity and Rationalisation. Issue 17 (29th April 2015) - Cowie, Thomas Y.; Kennedy, Lorna; Żurek, Justyna M.; Paterson, Martin J.; Bebbington, Magnus W. P.
Abstract: Crossed McMurry reactions of bifuran‐ or bithiophenedicarbaldehydes with bipyrroledicarbaldehydes have been studied for the first time. Only those porphycenic macrocycles derived from homocoupled McMurry products were formed. The results are explained by using both density functional theory and electron propagator computations to model the electron affinity of the dialdehyde starting materials. It was predicted that bifuran\bithiophene cross‐coupling would indeed occur, and this was demonstrated by the first synthesis of a novel dioxa, dithio hetero‐porphycenoid annulene. This approach will allow the prior identification of viable substrates for related crossed McMurry reactions. Abstract : In the first study of its type, experimental and computational studies on crossed McMurry reactions for the synthesis of porphycenoid macrocycles reveal a marked dependence of the product profile upon the reducibility of the dicarbonyl precursors.